2008
DOI: 10.2193/2008-007
|View full text |Cite
|
Sign up to set email alerts
|

Grizzly Bear Density in Glacier National Park, Montana

Abstract: : We present the first rigorous estimate of grizzly bear (Ursus arctos) population density and distribution in and around Glacier National Park (GNP), Montana, USA. We used genetic analysis to identify individual bears from hair samples collected via 2 concurrent sampling methods: 1) systematically distributed, baited, barbed‐wire hair traps and 2) unbaited bear rub trees found along trails. We used Huggins closed mixture models in Program MARK to estimate total population size and developed a method to accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 34 publications
10
133
1
Order By: Relevance
“…We collected hair only from the barbed wire and passed a flame under each barb after collection to prevent contamination between sessions. We compiled capture, telemetry, mortality, age, and past DNA detection data for 766 grizzly bears handled for research or management or identified during other hair sampling studies (Kendall et al 2008) in the NCDE during . Of the bears for which tissue samples were available, 426 were successfully genotyped at !7 loci for individual identification.…”
Section: Sampling Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We collected hair only from the barbed wire and passed a flame under each barb after collection to prevent contamination between sessions. We compiled capture, telemetry, mortality, age, and past DNA detection data for 766 grizzly bears handled for research or management or identified during other hair sampling studies (Kendall et al 2008) in the NCDE during . Of the bears for which tissue samples were available, 426 were successfully genotyped at !7 loci for individual identification.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Genetic distance to the Prophet River (P), British Columbia, grizzly bear population 1,150 km north of the NCDE was included for comparison with within-NCDE population distances. single sample, 2) pairs of individuals that differed at only 1 or 2 loci (1-and 2-mismatch pairs), 3) pairs of individuals that differed at 3 loci when those differences were consistent with allelic dropout (i.e., homozygous), and 4) individuals with samples geographically separated by large distances (Paetkau 2003, Roon et al 2005, Kendall et al 2008. We further minimized the risk of undetected genotyping error by replicating genetic data for all 17 markers (including gender) in !2 samples per individual or by repeating the analysis of all 17 markers in cases where just one sample was assigned to an individual.…”
Section: Genetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For large administrative units and for wide-ranging species, monitoring can represent a substantial challenge in terms of both resources and scientific methodology. Many management authorities rely on indirect methods, such as the collection of observation reports (e.g., Kindberg et al 2009) and harvest data (e.g., Cattadori et al 1999), as well as noninvasive field methods, including sign transects (Beier and Cunningham 1996), scent stations (e.g., Diefenbach et al 1994), camera traps (e.g., Karanth 1995) and noninvasive genetic sampling (NGS, e.g., Bellemain et al 2005, Kendall et al 2008. The latter entails the extraction of genetic material from hair, scat, and other sources of DNA, and has been implemented in numerous projects involving many species (review in Waits and Paetkau 2005).…”
Section: Introductionmentioning
confidence: 99%